Geriatric patients with free flap reconstruction: a comparative clinical analysis of 256 cases - Wähmann, Matthias Stefan Theodor; Wähmann, Melodie; Henn, Dominic; Xiong, Lingyun; Hirche, Christoph; Harhaus-Wähner, Leila; Kneser, Ulrich; Kremer, Thomas (Journal of reconstructive microsurgery, 2020)
Background In elderly patients, complex soft tissue defects are increasingly observed due to the prolonged life expectancy and accompanying comorbidities. The aim of this study is to evaluate whether free tissue transfer is safe in very old patients without additional risk and complications. Methods All patients older than 65 years undergoing free tissue transfer between November 2007 and September 2016 were reviewed in a retrospective study. Two cohorts were compared regarding perioperative morbidity and postoperative outcome (cohort 1 [old patients, ages 65-79]; cohort 2 [very old patients, ages ≥ 80]). Results In total, 256 patients were included in the study (cohort 1 [n = 217]; cohort 2 [n = 39]). Overall, 262 free flaps were performed due to a second microsurgical reconstruction in six cases. No statistically significant differences between cohorts were observed regarding surgical complications, total flap losses, and mortality. Detailed evaluation of cohort 2 revealed a significant learning curve during the observation period regarding the perioperative management and procedure of soft tissue reconstruction: operation length as well as postoperative intensive care unit stay decreased significantly over time (p < 0.05) and also surgical complications showed a positive trend (p = 0.07). We ascertained a shift toward a “more reliable” flap selection from predominantly anterolateral thigh flap) to axial flaps such as rectus abdominis and latissimus dorsi flaps. Conclusion Our study showed that age is not associated with an increased risk of postoperative complications. Reliable muscle free flaps, two-stage procedures, and safe vascular supply are important strategic aspects to achieve microvascular tissue transfer with high success rates in geriatric patients.